2019
DOI: 10.1111/disa.12398
|View full text |Cite
|
Sign up to set email alerts
|

The ethical contours of research in crisis settings: five practical considerations for academic institutional review boards and researchers

Abstract: The number of research studies in the humanitarian field is rising. It is imperative, therefore, that institutional review boards (IRBs) consider carefully the additional risks present in crisis contexts to ensure that the highest ethical standards are upheld. Ethical guidelines should represent better the specific issues inherent to research among populations grappling with armed conflict, disasters triggered by natural hazards, or health‐related emergencies. This paper seeks to describe five issues particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Their results suggest a general feeling that research in this setting is not only of particularly high social value, making it a desirable pursuit, but also necessitates a higher level of justification due to the inherent vulnerability of the research subjects [33]. There is also general agreement that the innate fluidity and urgency of humanitarian situations make swift and efficient ethics review of paramount importance [11,25,29]. Hunt et al report, "where research is launched in response to a sudden-onset disaster such as an earthquake or hurricane, researchers may need to initiate their protocols quickly in order to answer research questions pertinent to the acute phase of the disaster response" [11].…”
Section: Ethical Reviewmentioning
confidence: 98%
See 3 more Smart Citations
“…Their results suggest a general feeling that research in this setting is not only of particularly high social value, making it a desirable pursuit, but also necessitates a higher level of justification due to the inherent vulnerability of the research subjects [33]. There is also general agreement that the innate fluidity and urgency of humanitarian situations make swift and efficient ethics review of paramount importance [11,25,29]. Hunt et al report, "where research is launched in response to a sudden-onset disaster such as an earthquake or hurricane, researchers may need to initiate their protocols quickly in order to answer research questions pertinent to the acute phase of the disaster response" [11].…”
Section: Ethical Reviewmentioning
confidence: 98%
“…Discussion of the ethical review process was the most commonly identified theme, with 21 articles having a substantive focus on this [11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Independent ethics review prior to the start of a study is a core component of research ethics.…”
Section: Ethical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the ethics of research undertaken by and in collaboration with humanitarian actors has been increasingly discussed. These discussions are taking place against the backdrop of increased health and social science research as a result of the drive towards evidence-based humanitarian programming (Falb et al 2019). A range of governance approaches from guidelines to institutional ethical review processes have been developed which have been tailored to various stakeholders within humanitarian research, including non-governmental organisations (NGOs) (Schopper et al 2015), funding agencies, and the academic sector (Statement of Commitments from Humanitarian Scholars at World Humanitarian Summit 2016; Van Bavel et al 2016).…”
Section: Introductionmentioning
confidence: 99%